When to perform renal biopsy in patients with type 2 diabetes mellitus? Predictive model of non-diabetic renal disease - Florencio García-Martín; Esther González Monte; Eduardo Hernández Martínez; Teresa Bada Bosch; Norman E. Bustamante Jiménez; Manuel Praga Terente (Nefrología (English Edition), 2020)
Introduction: Diabetic nephropathy (DN) is one of the most frequent complications in patients with diabetes mellitus (DM) and its diagnosis is usually established on clinical grounds. However, kidney involvement in some diabetic patients can be due to other causes, and renal biopsy might be needed to exclude them. The aim of our study was to establish the clinical and analytical data that predict DN and no-diabetic renal disease (NDRD), and to develop a predictive model (score) to confirm or dismiss DN. Material and methods: We conducted a transversal, observational and retrospective study, including renal biopsies performed in type 2 DM patients, between 2000 and 2018. Results: Two hundred seven DM patients were included in our study. The mean age was 64.5 ± 10.6 years and 74% were male. DN was found in 126 (61%) of the biopsies and NDRD in 81 (39%). Diabetic retinopathy was presented in 58% of DN patients, but only in 6% of NDRD patients (p < 0.001). Patients with NDRD were diagnosed of primary glomerulopathies (52%), nephroangiosclerosis (16%), inmunoallergic interstitial nephritis (15%) and vasculitis (8.5%). In the multivariate analysis, retinopathy (OR 26.7; 95% CI: 6.8–104.5), chronic ischemia of lower limbs (OR 4.37; 95% CI: 1.33–14.3), insulin therapy (OR 3.05; 95% CI: 1.13–8.25), time course of DM ≥10 years (OR 2.71; 95% CI: 1.1–6.62) and nephrotic range proteinuria (OR 2.91; 95% CI: 1.2–7.1) were independent predictors for DN. Microhaematuria defined as ≥10 red blood cells per high-power field (OR 0.032; 95% CI: 0.01–0.11) and overweight (OR 0.21; 95% CI: 0.08–0.5) were independent predictors of NDRD. According to the predictive model based on the multivariate analysis, all patients with a score >3 had DN and 94% of cases with a score ≤1 had NDRD (score ranked from −6 to 8 points). Conclusions: NDRD is common in DM patients (39%), being primary glomerulonephritis the most frequent ethology. The absence of retinopathy and the presence of microhematuria are highly suggestive of NDRD. The use of our predictive model could facilitate the indication of performing a renal biopsy in DM patients. Resumen: Introducción: La nefropatía diabética (ND) es una complicación frecuente de la diabetes mellitus (DM), y su diagnóstico suele ser clínico. Sin embargo, en numerosas ocasiones la enfermedad renal que presentan los pacientes diabéticos es debida a otras causas cuyo diagnóstico es histológico. El objetivo del estudio fue determinar los datos clínicos y analíticos predictores de ND y enfermedad renal no diabética (ERND), y elaborar un modelo predictivo (score) para confirmar o descartar ND. Material y métodos: Estudio observacional, transversal y retrospectivo de biopsias renales realizadas en pacientes diabéticos tipo 2 entre 2000 y 2018. Resultados: Se incluyeron 207 pacientes diabéticos con una edad media de 64.5 ± 10,6 años; el 74% eran varones. La biopsia mostró ND en 126 (61%) y en 81 ERND (39%). La retinopatía diabética estaba presente en el 58% de los pacientes con ND y en el 6% del grupo con ERND (p < 0,001). Histología encontrada en la ERND: glomerulopatías primarias (52%), nefroangioesclerosis (16%), nefritis intersticial inmunoalérgica (15%) y vasculitis (8,5%). En el análisis multivariable, la retinopatía (OR 26,7; IC 95%: 6,8-104,5), la isquemia crónica de miembros inferiores (OR 4,37; IC 95%: 1,33-14,3), la insulinoterapia (OR 3,05; IC 95%: 1,13-8,25), una evolución de la DM ≥ 10 años (OR 2,71; IC 95%: 1,1-6,62) y la proteinuria nefrótica (OR 2,91; IC 95%: 1,2-7,1) fueron predictores independientes de ND. La microhematuria, definida como ≥ 10 hematíes/campo (OR 0,032; IC 95%: 0,01-0,11) y el sobrepeso (OR 0,21; IC 95%: 0,08-0,55) lo fueron de ERND. Según el modelo predictivo resultante del estudio multivariable para ND, el rango de puntuación varió de −6 a 8 puntos. Todos los pacientes con un score > 3 era tenían ND, y el 94% de los casos con score ≤ 1 punto fueron ERND. Conclusiones: La ERND es frecuente en pacientes con DM (39%). La etiología más frecuente son las glomerulonefritis primarias. La ausencia de retinopatía y la presencia de microhematuria son altamente sugestivas de ERND. La utilización de un sistema de puntuación facilita la indicación de biopsia renal en pacientes diabéticos.